2008
DOI: 10.1016/j.bbabio.2008.05.441
|View full text |Cite
|
Sign up to set email alerts
|

Looking for the minimum common denominator in haem–copper oxygen reductases: Towards a unified catalytic mechanism

Abstract: Haem-copper oxygen reductases are transmembrane protein complexes that reduce dioxygen to water and pump protons across the mitochondrial or periplasmatic membrane, contributing to the transmembrane difference of electrochemical potential. Seven years ago we proposed a classification of these enzymes into three different families (A, B and C), based on the amino acid residues of their proton channels and amino acid sequence comparison, later supported by the so far identified characteristics of the catalytic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
62
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(63 citation statements)
references
References 68 publications
1
62
0
Order By: Relevance
“…These facts indicate that all 3 families share a common chemistry for O 2 reduction and a universal mechanism for proton pumping. Based on such arguments, the proton-loading site and the kinetic gating elements also should be structurally conserved (25).…”
Section: Discussionmentioning
confidence: 99%
“…These facts indicate that all 3 families share a common chemistry for O 2 reduction and a universal mechanism for proton pumping. Based on such arguments, the proton-loading site and the kinetic gating elements also should be structurally conserved (25).…”
Section: Discussionmentioning
confidence: 99%
“…T he oxygen reductase members of the heme-copper superfamily are critical redox-driven proton pumps in the aerobic respiratory chains of most aerobic bacteria and archaea as well as in the mitochondria of eukaryotes (1)(2)(3)(4). These membranebound proteins catalyze the reduction of O 2 to water and use the free energy of this reaction to generate a proton motive force that is used for a number of essential biological functions, including the synthesis of ATP.…”
mentioning
confidence: 99%
“…The heme-copper oxygen reductases constitute a diverse group of phylogenetically related enzymes, the vast majority of which can be classified as members of the A-, B-, or C-family of hemecopper oxygen reductases (1,5,6). Enzymes from each of these oxygen reductase families have been shown to couple the redox chemistry to proton pumping (7)(8)(9)(10)(11).…”
mentioning
confidence: 99%
“…The active sites of both NOR and HCO contain a proximal histidine-coordinated heme and a distal three histidine-coordinated metal center. However, the metal center in HCOs is occupied by a copper (called Cu B ), whereas a nonheme iron is present in NOR (called Fe B ) (23,24). In addition, two conserved glutamates, shown by modeling to be close to the Fe B site (21, 22), are found to be essential for NOR activity (24,25).…”
mentioning
confidence: 99%
“…Bacterial NOR is a membrane-bound protein that catalyzes one step of this process, namely, the two-electron reduction of NO to N 2 O (17,19). With no crystal or solution structure available for bacterial NOR to date, sequence alignments and homology modeling (21,22) have indicated that NOR is structurally homologous to the largest subunit (subunit I) of hemecopper oxidases (HCOs) (23), enzymes that catalyze reduction of O 2 to water. The active sites of both NOR and HCO contain a proximal histidine-coordinated heme and a distal three histidine-coordinated metal center.…”
mentioning
confidence: 99%